Pengaruh Pajak Restoran, Pajak Hiburan, Pajak Hotel Terhadap Pendapatan Asli Daerah Provinsi Kalimantan Selatan - BRILLIANT ADIN RIJJAL; Novi Dirgantari; Eko Hariyanto; Edi Joko Setyadi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
In the execution of regional autonomy, local taxes and levies stand as crucial sources of local revenue aimed at financing various endeavors of local governance. The South Kalimantan Provincial Government has regional financial challenges in the future, in increasing the independence and optimization of its local taxes in order to increase PAD. The aim of this research was to investigate the impact of entertainment tax, restaurant tax, and hotel tax on regional original income. This study employed quantitative methods, utilizing secondary data extracted from the South Kalimantan regional government financial report (LKPD) spanning from 2019 to 2021.The sampling technique used is a saturated sample. the regression test results prove that restaurant and entertainment taxes have no effect on (PAD) while hotel taxes have a positive effect on (PAD). The limitation of this study is that the independent variables used are limited to three types of local tax variables, namely restaurant, entertainment and hotel taxes, without making demographic factors, area and income level as intervening or moderating variables. Local taxes will be able to have a positive influence if supported by adequate demographic and geographic factors.